Legionella occurrence in municipal and industrial wastewater treatment plants and risks of reclaimed wastewater reuse: Review. (1st February 2019) - Caicedo, C.; Rosenwinkel, K.-H.; Exner, M.; Verstraete, W.; Suchenwirth, R.; Hartemann, P.; Nogueira, R.
Abstract: Wastewater treatment plants (WWTPs) have been identified as confirmed but until today underestimated sources of Legionella, playing an important role in local and community cases and outbreaks of Legionnaires' disease. In general, aerobic biological systems provide an optimum environment for the growth of Legionella due to high organic nitrogen and oxygen concentrations, ideal temperatures and the presence of protozoa. However, few studies have investigated the occurrence of Legionella in WWTPs, and many questions in regards to the interacting factors that promote the proliferation and persistence of Legionella in these treatment systems are still unanswered. This critical review summarizes the current knowledge about Legionella in municipal and industrial WWTPs, the conditions that might support their growth, as well as control strategies that have been applied. Furthermore, an overview of current quantification methods, guidelines and health risks associated with Legionella in reclaimed wastewater is also discussed in depth. A better understanding of the conditions promoting the occurrence of Legionella in WWTPs will contribute to the development of improved wastewater treatment technologies and/or innovative mitigation approaches to minimize future Legionella outbreaks. Graphical abstract: Image 1 Highlights: Knowledge about the factors promoting Legionella´s growth in wastewater is limited. Aerobic wastewater treatment plants with temperatures >20 °C are sources of Legionella. Feasible control strategies for Legionella in wastewater systems should be developed. Regulations are necessary to establish discharge limits for Legionella in wastewater. Risk assessment of Legionella in reclaimed water systems should be further estimated.